Meningkatkan Percaya Diri Siswa Dengan Menggunakan Metode Bercerita - Rekayanti Putri Sandi; Geri Syahril Sidik; Riza Fatimah Zahrah (Lembaga Pengembangan Kinerja Dosen, 2023)
Student activity dominates and is very visible in learning. Having responsibility for the tasks that must be done by each student in the learning process makes students feel important and involved in the success of their learning. The objectives of this research are 1) to find out how lesson planning can increase students' self-confidence through the storytelling method and 2) to know how the implementation and improvement of learning can increase students' self-confidence through the storytelling method. The method used in this study is the Classroom Action Research (CAR) method. This research attempts to increase students' self-confidence through the storytelling method in thematic learning. The conclusion from this study is that researchers have used the storytelling method to increase students' confidence in learning Indonesian which is very good. The preparation made by the researcher was to prepare lesson plans (learning plans) related to increasing self-confidence in class.